Assessing the atrial substrate: electrograms from the coronary sinus can predict left atrial fibrosis. (25th November 2020) - Mohsen, Y; Draheim, J; Grossmann, N; Turan, C.H; Schoett, M; Horlitz, M; Stoeckigt, F
Abstract: Background: Left atrial fibrosis plays a key role regarding the success rate of pulmonary vein isolation for atrial fibrillation. It can be analyzed using LGE-MRI or invasive LA electroanatomical mapping. Assessing LA substrate prior to performing LA ablation procedures might help in optimizing the ablation approach. Method: We analysed highdensity-electroanatomical maps of the left atrium derived by Carto 3 from 282 consecutive atrial fibrillation patients scheduled for RF pulmonary vein isolation (PVI). Maps were divided into 5 different anatomical areas and fibrosis was defined as local voltage <0.5mV. The extent of fibrosis was analyzed and compared with signal recordings from different positions of a diagnostic catheter positioned in the coronary sinus (CS) using Pearson correlation analysis. Results: PVI was carried out in 282 patients (male 72%, mean age 63±10.8 years). A minimum of 1000 evenly distributed local electrograms were recorded in every patient. Significant LA fibrosis (>5%) was present in 54% of the patients with the maximum incidence of 100% at the anterior and 80% at the posterior wall. Signal amplituds in the proximal CS position significantly correlated with presence of LA fibrosis in the posterior LA (R 0.84, p<0.001), LA roof (R 0.65; p<0.001), left lateral (R 0.54; p<0.001), septal (R 0.47; p<0.001), and even LA anterior wall (R 0.56; p<0.001). Comparable results were found when using distal CS signals or a signal averaged over all individual CS signals. When used as a diagnostic tool, a CS amplitude <1.9mV could predict fibrosis at the posterior left atrial wall with a specificity of 97% and a sensitivity of 67% (PLR 24, AUC 0.91, 95% CI 0.87 - 0.95; p<0.001). A cut-off value of 1.9mV could be used to identify patients with only minimal LA fibrosis (<5%) with specificity of 88% and a sensitivity of 50% (PLR 4.2, AUC 0.81, 95% CI 0.71–0.89; p<0.001. Conclusion: Voltage signals in the CS are significantly associated with presence of fibrosis in all left atrial areas. Moreover, CS voltage signals can be used to identify presence of significant left atrial extrapulmonary vein fibrosis and could help guiding left atrial ablation procedures and choice of ablation technique. Funding Acknowledgement: Type of funding source: None